UTILIZING DIGITAL TECHNOLOGY TO ENHANCE ECONOMIC COMPETITIVENESS AND BUSINESS SUSTAINABILITY AMIDST TECHNOLOGICAL DISRUPTION FOR SMES (SMALL AND MEDIUM ENTERPRISES) - Triana, Dewi; Linawati, Linawati (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
This literature review discusses the role of digital technology utilization in enhancing economic competitiveness and business sustainability amidst technological disruption. The purpose of this study is to identify the role of digital technology utilization in improving economic competitiveness and business sustainability in the face of technological disruption. The research method used is a literature review by collecting data from relevant national and international sources. This study shows that the use of digital technology can increase productivity, operational efficiency, product quality, create new opportunities to expand markets, and improve decision-making quality. However, many industries invest resources in the latest technology, but without proper management, disruption can lead to instability, resulting in an inevitable consumer manifesto. The implementation of digital technology also faces numerous challenges, such as resource shortages, unsupportive policies, lack of investment in research and development, and insufficient awareness of the importance of innovation. Therefore, enhancing economic competitiveness through the utilization of digital technology requires the involvement of all parties, such as the government, educational institutions, the private sector, and the general public. The government must create policies that support innovation, improve access to resources, and increase support for research and development to ensure business sustainability in the face of technological disruption.